KEADILAN RESTORATIF DALAM PENEGAKAN HUKUM PEMILU - Kania, Dede (Bawaslu Provinsi Jawa Barat, 2022)
Election law enforcement is one of the important principles for fair elections. In its form, election law enforcement includes election criminal law enforcement. Regulations regarding election criminal law based on Law Number 7 of 2017 are based on retributive justice. In its development, the basis of criminal justice has now begun to change towards restorative justice. This restorative justice aims to provide a form of justice and restoration to victims, by placing perpetrators and victims on an equal footing in the case settlement process. This study uses a juridical method, namely research on positive legal principles and legal principles. In addition, legal interpretation and legal philosophy are also used. The results of the study show that the use of restorative justice for the enforcement of election criminal law in the 2024 election is still not possible, due to the unavailability of an adequate legal basis. Amendments to Law 7 of 2017 must be made to the form of justice that is to be realized. Apart from that, it is necessary to regulate a case settlement mechanism that is capable of realizing restorative justice. However, prevention efforts can be carried out by election supervisors, to minimize the number of cases that must be resolved.